ANALYZING THE IMPACT OF FASHION INFLUENCER ON ONLINE IMPULSIVE BUYING BEHAVIOR - Prihana Gunawan, Najla
As the internet has growth expeditiously, many people use the internet also for running their business and use one of the most powerful platforms on the internet, which is social media. The growth of social media has created opportunities for online shop seller to sell their product on Instagram. And to market, their product, online seller endorsing people that interested in fashion and can give influence to their followers, also has more than a thousand followers on Instagram, called Fashion Influencer. One of the main reason why people buy a product is because of the recommendation of fashion influencer on social media, people buy for something that they don’t intend to buy it. And the impulsive buying behavior happens. This research aims to analyze the impact of two types of fashion influencer on Instagram, namely micro influencer, and macro influencer to impulsive buying behavior and related to the fashion adaptation style by the online consumer using a diffusion of innovation theory. This research used a qualitative approach with a semi-structured and in-depth interview, coding interpretation to analyze the interview result with a total of 20 participants and quantitative approach through a questionnaire to validate the data by knowing the percentage of consumer based on the sample was conducted. The sample of this research is female in Jakarta and Bandung with age of 18-22 years old and ever purchase product impulsively affected by fashion influencer. The result of coding interpretation and questionnaire shows that 80% of participants are adopting the fashion product and influenced by a purely specific influencer that leads to impulsive buying. Results indicate that macro influencer affects the impulsive purchase of fashion product to early majority stage and self-updated stage. Micro influencer affects the impulsive purchase of fashion product to early adopter fashion adaptation stage and leads to pure impulsive buying of the consumer. Micro Influencer is playing a bigger role in persuading the consumer to become more impulsive in purchasing a fashion product online. When micro influencers promoting a product, early adopter fashion adaption stage consumer sees the promotion, most of them are directly and spontaneously bought the product that promoted by micro influencer just because they don’t want to others wear the same products as they are. The findings of this research will be useful for fashion influencer and Instagram online shop seller to maximize their marketing strategies that fit their target market and enhance the knowledge of customer about their buying behavior.